2007
DOI: 10.1111/j.1365-2443.2007.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Chk2 kinase is required for methylglyoxal‐induced G2/M cell‐cycle checkpoint arrest: implication of cell‐cycle checkpoint regulation in diabetic oxidative stress signaling

Abstract: Methylglyoxal (MG) is a reactive endogenous metabolite that is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…The efficiency of the aphidicolin and nocodazole treatments was determined by examining the percentage of cells undergoing mitosis by immunofluorescence analysis of DAPI-stained cells. In agreement with published results, we found that the number of HEK-T, HEK-TPKD and HEK-TPKD3 cells undergoing mitosis reached a peak (20–30%) between 12–14 h after aphidicolin removal [22,23] and 50–70% 12 h after nocodazole incubation [2628]. IEC-18 cells were synchronized at G 1 /S using the procedure described above for HEK-293 cells.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…The efficiency of the aphidicolin and nocodazole treatments was determined by examining the percentage of cells undergoing mitosis by immunofluorescence analysis of DAPI-stained cells. In agreement with published results, we found that the number of HEK-T, HEK-TPKD and HEK-TPKD3 cells undergoing mitosis reached a peak (20–30%) between 12–14 h after aphidicolin removal [22,23] and 50–70% 12 h after nocodazole incubation [2628]. IEC-18 cells were synchronized at G 1 /S using the procedure described above for HEK-293 cells.…”
Section: Methodssupporting
confidence: 90%
“…After aspirating the final wash, the cells were incubated in fresh medium with 10% FBS, supplemented or not, with 100 ng/ml Tet plus aphidicolin and cell lysates obtained at the indicated times by lysing the monolayers in 2× SDS-protein sample buffer. A synchronization protocol previously described [20] was used to obtain G 2 /M HEK-293 derived cultures [2628]. Briefly, cells plated in 60-mm dishes at 1.5×10 5 cells/dish in complete medium were incubated for 18–20 h at 37 °C before being rinsed 3× with DMEM and incubated in DMEM supplemented with 0.2% FBS, plus or minus Tet (100 ng/ml), for 36 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, ATM was shown to be downstream of platelet-derived growth factor beta (PDGF beta) receptor activation by hydrogen peroxide, which leads to the phosphorylation and activation of the p53 [63]. In mammalian cells, oxidative stress also leads to the activation of MAP kinases, p38 MAPK and JNK pathways, which might contribute to the activation of ATM through crosstalk between these pathways [64,65].…”
Section: Atm Deficiency and Oxidative Stressmentioning
confidence: 99%
“…The deleterious effect of MG on different types of cells has been extensively studied [30], [31], [32]. A previous study reported an increased apoptotic cell number when mouse Schwann cells were treated with 500–1000 µM MG [31].…”
Section: Discussionmentioning
confidence: 99%
“…An inhibitory effect of MG on cell growth by inducing apoptosis was studied [30], [31], [32]. It is reported that MG promoted programmed cell death through several signaling pathways including growth factor receptor and the gp130/STAT3-signaling pathway.…”
Section: Introductionmentioning
confidence: 99%